Social Security as a Guarantee of Stable Economic Situation of the Family - Waldemar A. KUNZ (Communications of International Proceedings, 2021)
In the modern world the aspects of economic, social and economic security are counted among the most important factors of socio-economic development. Overlooking this issue and not taking it into account in everyday decisions creates a serious barrier to economic and state development. Despite the fact that this issue is in fact quite complicated, its implementation is possible and necessary. The beneficiary of these actions is, of course, the society, which through a significant improvement in the sense of security and the related improvement in the quality of life, in a favorable natural, professional, family and social environment, culture, community belonging, has a sense of harmonious life and opportunities for personal development. The purpose of the article is to show the causal context of the impact of social security as a stabilizer of the economic situation of the individual and the family, in the aspect of socio-economic development of the state.
Keywords: Economy; Security; Family; Development.